Evolução da demanda ao Curso de Graduação em Enfermagem da Universidade Federal de São Carlos Evolution of demand for the nursing undergraduate course of Federal University of São Carlos - Edmar Vieira dos Santos; Sonia Maria Arantes Almeida (SciELO, 1997)
O estudo analisa a evolução da procura pelo Curso de Graduação em Enfermagem da Universidade Federal de São Carlos (UFSCar), desde o 1º vestibular em 1977 até 1996. Nessa análise serão utilizados comparativamente os dados dos Cursos da Universidade de São Paulo (USP) e da Escola Paulista de Medicina, atualmente denominada Uiversidade Federal de São Paulo (UNIFESP). A crise econômica e do setor da saúde influíram significativamente na queda súbita da procura pelos Cursos na década de 80. Em 1990 o vestibular da UFSCar passou a ser realizado pela Fundação Universitária para o Vestibular (FUVEST). Nesse ano a relação candidato/ vaga atingiu seu nível mais baixo, desde 1977. A partir de 1991, a tendência de retomada do crescimento econômico, e a implantação do Sistema Único de Saúde (SUS) determinaram o crescimento da demanda. Dos três cursos da carreira da Enfermagem na FUVEST, o da UFSCar que é o único do interior do Estado, ainda é o mais procurado em 3ª opção, apesar da procura em 1ª opção ter passado de 2,0 em 1990 para 6,0 em 1995, caindo para 4,6 em 1996. A pouca procura em 1990; os critérios de corte e o procedimento de chamada dos candidatos classificados concorreram para que das 30 vagas oferecidas fossem repreenchidas apenas 15, mesmo com dois vestibulares. This study analyzes the evolution of demand for the nursing undergraduate course of Federal University of Sao Carlos (UFSCar), from the first entrance examination in 1977 to 1996. The economic crises and the crises in health social programs affected significantly the demand for this entrance examination which declined abruptly 1980. During 1990, the demand for this nursing program was two candidates per chair, the lowest level since its foundation in 1977. From 1991, the recovery of the Brazilian economy associated with a change in the health care system were responsible for the increasing in the demand of nursing professionals. In 1990 the entrance examination started to be done by another institution (FUVEST, one state foundation responsible for this examination). The FUVEST was already responsible for the entrance examination for two others São Paulo State Universities. Starting in 1990 the candidates could compete simultaneously for the nursing program at the three universities through the same entrance examination. The UFSCar always was the last option for the candidates among those universities. However, the candidate demand for that program at UFSCar, as the first option, increased to six candidates per chair in 1995 with a small decrease in 1996 (4,6 candidates/chair). During 1982 and 1986, respectively three and six chairs, out of 30 offered by UFSCar, were not taken, this number increased to 15 during 1990. This great decrease in the interest for this nursing program, during 1990 could be attributed to three factors: First, the decrease in the candidate numbers that applied for this examination (around 2/1). Second, the degree of difficulty of the examination requirement. Third, the bureaucratic procedures that the candidates had to fultill, after being approved, to get enrolled in the program.